A Critical Review on the Regulatory and Legislation Challenges Faced by Halal Start-up SMEs Food Manufacturers in Malaysia - Nazatul Shima, Abdul Rani; Chon, Lok Siaw (2012)
In Malaysia, there is little research done on the journey of the small and medium industries start-up challenges and success. Therefore this paper is a critical review of the regulatory and legislation challenges faced by halal food manufacturing industries in Malaysia. The regulatory challenges that are discussed in this paper include the licenses from Islamic Department Malaysia (Jakim), Department of Environment (DOE), Local Council (Majlis Daerah) and Ministry of Health (MOH).SMEs start-ups have to meet all these challenges in their first three years of operations in addition to other challenges such as finance, marketing, technology, production, operations and management.